Redesain Pasar Tradisonal Kara Wutung Di Adonara Kabupaten Flores Timur Dengan Tema Hemat Energi - Belun, Dedianus Masang; Dede, Petrus Jhon Alfred Depa; Kurniawan, DVX. Deddy (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2022)
Kara Wutung traditional market, is one of the traditional markets on the island of Adonara, East Flores Regency, East Nusa Tenggara Province. This market plays a very important role in meeting the living needs of the people around the island of Adonara. This market serves as a buffer for the community's economy and is one of the sources of income for local governments. The main problem of Kara Wutung market is that the indoor space of the market during the day is seen in dark, stuffy, hot and smelly conditions, this is due to the lack of openings for natural lighting and circulation for air in and out. These spaces must require artificial lighting during the day such as lights and artificial lighting such as fans and air conditioners to reduce hot air temperature conditions. In redesigning this market by choosing an energy-saving theme. The selection of this theme aims to minimize the consumption ofenergy used for theuse of electric lights, air conditioners / fans. The reduction in energy use, especially during the day, is carried out by utilizing natural lighting from the sun and natural lighting from the wind. This method of design is carried out by analyzing data by means of; quantitative analysis, qualitative analysis, and comparative analysis. Data collection is carried out by means of; literature studies, interviews, as well as observations. After conducting the analysis, the next stage is to draw up the concept of planning and designing. From the results of the design at the Kara Wutung traditional market using energy-efficient design concepts and strategies, it has provided the right solution to the problems that occur in the Kara Wutung traditional market. The application of design concepts and strategies is carried out in ways such as; utilizing naturallighting with the addition of skylight on the roof of the building, the use of vegetation as a sunlight filter. Focusing on the wide openings in the building, placing the building extending from the north south direction, the building is designed with a dominant flat plane shape and rectangular and a gable roof with openings above the roof so that air circulation can easily go in and out.